Financial Incentive Policy to Encourage Circular Economy of MSMEs in Rural Areas - Sofyana Nurranti; Dian Purnomo Jati (Jurnal Akuntansi, Manajemen dan Ekonomi, 2026)
This study aims to analyze various financial incentive policies that can be utilized to promote the implementation of circular economy practices among Micro, Small, and Medium Enterprises (MSMEs) in rural areas. Using a descriptive qualitative approach based on literature review, the research examines the effectiveness of various incentive mechanisms such as tax subsidies, low-interest microcredit, revolving village funds, and public-private partnerships implemented in Indonesia and ASEAN countries. The study also evaluates the challenges faced in the implementation of these policies and identifies the prerequisites for the successful deployment of financial incentives in supporting circular economy innovations among rural MSMEs. Findings indicate that appropriately designed financial incentives not only enhance MSMEs' interest in adopting circular business models but also strengthen multisectoral collaboration toward achieving sustainable rural economic development. This research provides practical recommendations on effective incentive policy design and underscores the crucial role of fiscal policies and institutional collaborations in accelerating the transition to a circular economy.